Outer membrane permeability of mcr-positive bacteria reveals potent synergy of colistin and macromolecular antibiotics against colistin-resistant Acinetobacter baumannii - Li, Meisong; Ma, Furong; Zhao, Hui; Zhou, Dianrong; Liang, Lujie; Lv, Runling; Li, Jiachen; Wang, Yaxuan; Xu, Lin; Liu, Chenfei; Tian, Guo-Bao; Feng, Siyuan; et al. (Frontiers in Microbiology, 2024)
Colistin (CT) is the last-resort of antibiotic against multidrug-resistance (MDR) Acinetobacter baumannii (A. baumannii) infection. However, colistin resistance is increasingly reported in A. baumannii isolates partially due to the global emergence and dissemination of plasmid-borne mobile colistin resistance (mcr) gene and is a threat to human health. Thus, available treatment strategies urgently required in the fight against colistin-resistant A. baumannii. Here, we showed that mcr confers damaged outer membrane (OM) permeability in A. baumannii, which could compromise the viability of A. baumannii. Consistently, A. baumannii with colistin resistance exhibits increased susceptibility to macromolecular antibiotics such as rifampicin (RIF) and erythromycin (ERY). Moreover, the combination therapy of colistin and rifampicin demonstrates efficacy against colistin-resistant A. baumannii, regardless of the presence of mcr. Altogether, our data suggest that the synergy of colistin in combination with macromolecular hydrophobic antibiotics poses a promising therapeutic alternative for colistin-resistant A. baumannii.